Evolution and trends of information systems for business management: the mbusiness. a review (2010)
This article makes a review from the origin to currently of information systems for business management. It is specially emphasized about the changes that have occurred in recent years in such kind of systems and in what are the trends for the coming future. Between this trends it is possible identify several technical advances and new functionalities that are being joined or that will be soon. For example, a new functionality or advance that is incorporating is the mcommerce, which not only can influence the information system in a high degree but also in the strategies and management activities of currently companies.